2009
DOI: 10.1245/s10434-009-0446-0
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Expression of RNA-Binding Protein IMP3 Predicts High-Stage Lymph Node Metastasis and Poor Prognosis in Colorectal Adenocarcinoma

Abstract: Diffuse IMP3 protein expression correlates with invasion and aggressiveness during cancer growth and metastasis, and it is an important prognostic factor of CRAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 34 publications
6
47
0
Order By: Relevance
“…Also, our results showed a relationship between the grade of the tumor differentiation and IMP3 immunoreactivity, while this relationship was not found by the studies of Lin et al (23), Li et al (24) and Yuan et al (25). Consistent with the study of Lochhead et al (22) and Lin et al (23) and in contrast with the research of Yuan et al (25), there was no relationship between tumor size and the grade of tumor differentiation in the present study. In contrast with the study of Lochhead et al (22) and Lin et al (23) an insignificant correlation between the depth of tumor and lymph node involvement was found.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, our results showed a relationship between the grade of the tumor differentiation and IMP3 immunoreactivity, while this relationship was not found by the studies of Lin et al (23), Li et al (24) and Yuan et al (25). Consistent with the study of Lochhead et al (22) and Lin et al (23) and in contrast with the research of Yuan et al (25), there was no relationship between tumor size and the grade of tumor differentiation in the present study. In contrast with the study of Lochhead et al (22) and Lin et al (23) an insignificant correlation between the depth of tumor and lymph node involvement was found.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that IGF2BP3 is a prognostic and diagnostic biomarker in many tumoral tissues including colorectal adenocarcinoma (22)(23)(24)(25). We stained 112 formalin fixed paraffin embedded colorectal tumor tissues (NOS type) with an immunohistochemistry method and showed that 50% of these tumors were cytoplasmically positive for IMP3.…”
Section: Discussionmentioning
confidence: 96%
“…(9,10,(12)(13)(14)(30)(31)(32) Vikesaa et al also showed that IMP3 could regulate the adhesion and invasion of HeLa cells by directly targeting CD44 in the formation of invadopodia. (11) In our previous study, we showed that IMP3 expression promoted tumor invasion and predicted early recurrence and poor prognosis in hepatocellular carcinoma and that the invasion ability could be suppressed by depletion of IMP3 expression in vitro by RNAi.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that IMP3 is associated with aggressive and advanced carcinomas in colon, kidney, neuroendocrine skin (Merkel cell carcinoma), liver, bladder, ovary, and in soft tissue sarcomas [16][17][18][19][20][21][22][23][24][25]. On the basis of these results, IMP3 may be a useful prognostic factor in many malignant solid tumors.…”
Section: Introductionmentioning
confidence: 99%